Keeping Narcissism at Bay: Kant and Schiller on the Sublime (Konturen, 2010)
This essay considers the sublime as a veiled form of narcissism. Both narcissism and the sublime test and reveal the limits of the concept of the self and both can be viewed as attempts to transcend the borders of the self. Yet while narcissism has been defined as a “failure of spiritual ascent” (Hadot), the sublime has been used to transcend the limitations of the self by pointing to its infinite potential. The essay explores how the sublime in Immanuel Kant’s and Friedrich Schiller’s aesthetics relies on narcissistic impulses by creating a male inner self and protecting it from the stigma of vanity. I propose that their use of this aesthetic category helped objectify an essentially subjectivist aesthetics. Yet while Schiller follows Kant in deriding the sensual aspects of human nature as egotistical and amoral, Schiller’s dramas also challenge some of the Kantian premises. When Schiller’s protagonists sacrifice lives in the service of ethical ideas, the sublime’s oppressive spirit reveals itself.